Organizational Change and Reference-Dependent Preferences - Klaus Schmidt; Jonas von Wangenheim (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Reference-dependent preferences can explain several puzzling observations about organizational change. We introduce a dynamic model in which a loss-neutral firm bargains with loss-averse workers over organizational change and wages. We show that change is often stagnant or slow for long periods followed by a sudden boost in productivity during a crisis. Moreover, it accounts for the fact that different firms in the same industry often have significant productivity differences. The model also demonstrates the importance of expectation management even if all parties have rational expectations. Social preferences explain why it may be optimal to divide a firm into separate entities.
Keywords: D23; D91; L2; 330; organizational change; productivity; reference points; loss aversion; social preferences